ÙØ¹Ø§Ù„ÙŠØ© Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØµÙˆØ±Ø© ÙÙŠ Ù„Ø¹Ø¨Ø© Ø§Ù„ØªØ®Ù…ÙŠÙ† Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ù„ØªØ±Ù‚ÙŠØ© ÙƒÙØ§Ø¡ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª - Nurul Aini; Raudatul Jannah; asriandi asriandi (Lughatu Ad-dhat, 2021)
The educational process is not isolated from the role of teaching aids in it, because the teaching aid is an integral part of the school’s education process. The position of the educational medium in the parts of the study process was an effort to strengthen cohabitation between the teacher and the student and between the student and his home. This research was conducted in the research of guessing words in the promotion of Arabic vocabulary through the means of pictures among students in the Islamic High School of Bibidas. The use of the means of images in teaching Arabic aims to master the students in vocabulary, ie facilitating them in learning Arabic vocabulary effectively. The research in the Islamic High School of Pipidas aimed to describe how to use the medium of pictures in teaching the Arabic language in order to master vocabulary at the Islamic High School of Pipidas. The type of this research was quantitative research wherever the researcher made observations in the field of research to obtain data and information related to the existing research. The existing data collection method is observation and documentation. The results of the research indicate that the implementation or application of the use of the image method in teaching Arabic in the Islamic High School of Bibidas is effective, as it was for the sake of mastering Arabic vocabulary. The first step is to create the Instructional Design Professor (RPP) in relation to the learning objectives. The second step is to implement or apply the use of the image media, which was effective in benefiting the class and facilitating the students in understanding and memorizing the vocabulary.